The value of serological markers (CA19-9 & CCSA4) in the screening and prognosis of colon cancer - AL-Obaidy, Athraa A. M; AL-Hadithi, Hayfaa S.; Mahmood, Aqeel Sh. (Journal of the Faculty of Medicine Baghdad, 2017)
Background:- Colonic cancer is a very common disease world-wide being fourth most common cancer characterized by abnormal proliferation of the inner wall of colon at beginning then taking full colon wall thickness then to surrounding lymph nodes and tissues and finally metastasis.Objective:- To evaluate the efficacy of serum CA19-9 and CCSA-4 levels in the screening and prognosis of colonic cancer and their validity for this.Patients and methods:-This study was applied on 35 patients with colonic cancer, 35 patients with benign polyps and 16 negative controls. All individuals were subjected to blood sampling for measuring their serum CA19-9 and CCSA-4 using ELISA technique.Results:-Our study shows that colonic cancer patients presented at ages between 53-82 years of age (mean 68.5). Serum levels of CCSA-4 were significantly elevated in those patients with advancing stages (C&D) compared with stages (A&B) and lower levels found in patients undergone surgical removal of tumor or received chemotherapy.Also a positive relation found between CCSA-4 with alcohol intake and smoking. Less significant levels and relations found with CA19-9.Conclusion:-Serum CCSA-4 is sensitive and specific indicator for diagnosis, prognosis and screening of colonic cancer.